PENERAPAN PIDANA PENGGANTI DENDA BERUPA PENYITAANHARTA TERPIDANA DALAM TINDAK PIDANADI BIDANG PERPAJAKAN - Iwan Yuhandri (2021)
This research was conducted to find out the application of criminal penalties in the form of confiscation of the convict's property and imprisonment in lieu of fines in criminal acts in the taxation sector and to find out how the application of criminal penalties in lieu of fines in the form of confiscation of the convict's assets in criminal acts in the field of taxation that has not been regulated in law General Provisions on Tax Procedures (UU KUP). This gives rise to different opinions among judges in making their decisions, giving rise to legal uncertainty. The method used in this paper uses normative legal research, with a statute approach and a case approach, using primary legal materials, with data collection by library research, then analyzed using qualitative methods. Judges in imposing a fine in lieu of a fine in a tax crime, there are two different opinions in the court's decision, namely: First, a decision that directly subsidizes the confiscation of the convict's property if the convict does not pay the fine; Second, immediately subsidize confinement in lieu of fines if the convict does not pay the fine, without confiscating the convict's property. Imprisonment in lieu of a fine refers to Article 30 and Article 31 of the Criminal Code (KUHP).